Pengendalian Agronomik Melalui NPK Susulan dan Waktu Panen dalam Menghasilkan Vigor Benih Kedelai - Yayuk N.; N. Nurmauli (Jurnal Penelitian Pertanian Terapan, 2010)
The objective of this study was to evaluate the effect of dosages NPK and harvest day on seeds viability. The study was conducted at the experiment station of Polinela, Bandarlampung and Seed Laboratory, Unila from Januari to June 2008.Treatment consicted of two factors arranged in factorial design (5x7). A Split plot design with three replications was used. The main plot factor was NPK dosages, i.e., 0, 25, 50,75, and 100 kg.ha-1. The Subplot factor was harvest day, i.e., R7, R8, R8+3, R8+6, R8+9, R8+12, R8+15. Examination of hypothesis done with regression analysis at significance level 5%. Interaction between fertilizer doses NPK supplement and harvest day influences initial vigour of variety soy seed Anjasmoro. Germanation uniform and germination speed can be improved with addition of NPK supplement to 100 kg/ha though harvested at R8+15 day while at harvesting since R8 until R8+12 day, initial vigour not reality; phase R8 or day 81stafter planting. Harvest day 88-89th after planting or R8+15 day to yield maximum initial vigour based on variable germination speed ( 30,19 %/day) if dose NPK supplement is improved to 100 kg/ha. Harvest R7, germination seed are still increase at various doses NPK supplement while harvesting since R8 until R8+15 day, the influence of germinates power is not significant. Keywords: fertilization, seed, soybean, harvest